Organophosphorus Poisoning Requiring Very High Dose of Atropine: A Case Report - Kandel, Gobinda; Poudyal, Sunil; Basnet, Raju; Shah, Sunil Kumar (Journal of Bharatpur Hospital, 2025)
Organophosphorous compounds are easily available in Nepal. Intake of op compounds is a commonest mode of suicide. Atropine, oximes and other supportive care are corner stones in management of op poisoning. We present a case report of an adult man with op poisoning requiring very high dose of atropine and treated successfully. Atropine in high dose is safe and effective antidote in management of op compound poisoning.